The Politics of Tax Criminal Law in Indonesia - Jiwar, Syarif (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This paper's research is titled The Legal Policy of Tax Criminal Law in Indonesia. The focus of this research is to discover and analyze the legal policy of criminal law in the field of taxation in Indonesia including the criminalization of specific behaviors within the scope of applying rights and obligations in the field of taxation. This research uses a normative legal method with a literature approach to analyze the political choice of tax criminal law in Indonesia. The data used is secondary data, including primary legal materials such as tax regulations and secondary legal materials such as literature and other relevant documents. This legal study points out that Indonesia met two stages of criminal legal policy in the field of taxation, which means the pre-tax reform phase and the tax reform phase, both of which were affected by both internal and external factors.